A Comparative Clinical study of Lakshadi Lepa and Panchanimba Ghana vati in Mukhdooshika w.s.r to Acne Vulgaris - Tiwari, Divya; Sharma, Anita; Charak, Sandeep (International Research Journal of Ayurveda & Yoga, 2024)
In Ayurveda, mukhadushika is mentioned under the heading of Kshudra rogas, characterized by Shalmali thorn-like eruption on the face due to vitiation of kapha, vata, and rakta in adolescence, called as mukhdushika/yuvan pidika. In this study, 2 trial drugs were taken for Mukhdooshika which has been mentioned in Samhitaas. Aims and Objective: This study is to assess the efficacy of Lakshadi Lepa and Panchanimbadi Ghana Vati along with the comparison with Acnovin ointment and capAcnovin. Materials and Methods: This study was an open randomized control clinical trial. Total 30 patients were selected and divided into 2 groups randomly 15 patients in each group, to compare the clinical efficacy of study drug Group A with study drug Group B along with kumkumadi taila nasyam for 1 month in the management of Mukhdooshika (Acne). The results of therapy have been evaluated by statistical methods in 2 steps. 1st step is evaluating within the group before and after treatment in both groups separately and in 2nd step the evaluations of inter-group/between 2 groups evaluation of both therapies. Results: In both study and control group, 0% of patient showed excellent relief. 6.66% and 13.33% patients showed marked relief in study and control groups, respectively. 60% and 40% patients showed moderate relief in study and control groups, respectively. 33.33% and 46.66% patients showed mild relief in study group and control group, respectively, and the percentage of no relief patient was zero in both groups.